DANCE VOCABULARY: FOLKLORE, CHERACTER DANCE AND CONTEMPORARY DANCE - Yordanova, Julia (E-Journal VFU, 2025)
The article examines the development of the dance lexicon as a dynamic and diverse phenomenon, combining elements of folklore, character, and contemporary dance. It analyzes works such as 'Zorba the Greek,' 'Napoli,' and 'Nestinarka, 'Carmen which illustrate the interaction between tradition and modernity. The article explores the architectonic principles of folklore dances, the importance of technical preparation, and the role of emotional expressiveness in contemporary dance theater.
Keywords: dance lexicon; folklore; character dance; contemporary dance; stage art